Kepastian Hukum E-Akta Notaris Sebagai Alat Bukti Autentik Dalam Sistem Pembuktian Perdata di Indonesia - Ali Munib; Samsul Huda (Policy and Law Journal, 2025)
The advancement of digital technology has driven the transformation of notarial practice toward the use of Electronic Notarial Deeds (E-Deeds) as part of the modernization of civil law in Indonesia. However, the absence of explicit legal provisions regarding their status and evidentiary power creates legal uncertainty. This study aims to analyze the formal and material validity of E-Deeds in relation to the civil evidentiary system and to formulate a normative framework ensuring their legality and authenticity. The research employs a normative juridical method with statutory and conceptual approaches, utilizing primary, secondary, and tertiary legal materials. The findings reveal that E-Deeds may be recognized as authentic evidence if they satisfy both formal and material validity requirements, are supported by certified digital security systems, and are regulated within a harmonized legal framework between the Notary Law and the Electronic Information and Transactions Law (ITE Law).